2017
DOI: 10.15171/jlms.2017.s2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Photodynamic Therapy in the Treatment of Chronic Periodontitis: A Review of Literature

Abstract: Introduction: Chronic periodontitis is the most common periodontal disease which is related to the chronic accumulation of bacterial plaque. Since mechanical methods are not sufficient in the treatment of this disease, administration of local/systemic antibiotic is recommended following mechanical debridement. However, side effects of antibiotics such as microbial resistance and patient allergy led to development of alternative methods. One of these suggested methods is the antimicrobial photodynamic therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 31 publications
(29 reference statements)
1
31
0
2
Order By: Relevance
“…In our study, the progress was made in reducing CAL in the test group more than in the control group three months after the initial treatment (p < 0.05). The reduction matches the previous systematic reviews on SRP with different adjuncts, showing that a three-month therapy leads to the CAL value ranging 0.08-1 mm [22,23]. Our results demonstrated CAL gain by es much as 0.9 mm, representing better outcome compared to the control group with only 0.33 mm reduction.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the progress was made in reducing CAL in the test group more than in the control group three months after the initial treatment (p < 0.05). The reduction matches the previous systematic reviews on SRP with different adjuncts, showing that a three-month therapy leads to the CAL value ranging 0.08-1 mm [22,23]. Our results demonstrated CAL gain by es much as 0.9 mm, representing better outcome compared to the control group with only 0.33 mm reduction.…”
Section: Discussionsupporting
confidence: 88%
“…Along this line, light-based therapeutics have gathered enormous interest from researchers in the past two decades for various biomedical applications such as diagnosis, drug delivery, and imaging, among others. These treatment strategies, particularly photothermal therapy (PTT) and photodynamic therapy (PDT) [ 1 ], have emerged as promising alternatives to the traditional chemotherapeutic approaches and surgery practices, due to beneficial properties such as minimal invasiveness [ 2 , 3 , 4 ], high efficacy [ 3 , 4 ], preferential localization [ 5 , 6 ], excellent tissue penetration [ 7 , 8 , 9 , 10 ], and improved patient compliance [ 2 , 4 , 5 , 11 , 12 ]. Oftentimes these strategies are controlled by using specific sensitizers that are preferentially located at the desired site and subsequently activated in the presence of light to perform their therapeutic duties.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the researchers suggested that a combination of both treatment methods would yield better results for the NPT of aggressive periodontitis. So, the use of PDT in the treatment of periodontal diseases is still an object of interest .…”
Section: Introductionmentioning
confidence: 99%